Visual speech cues speed processing and reduce effort for children listening in quiet and noise. (30th July 2020) - Holt, Rebecca; Bruggeman, Laurence; Demuth, Katherine
Abstract: Processing speech can be slow and effortful for children, especially in adverse listening conditions, such as the classroom. This can have detrimental effects on children's academic achievement. We therefore asked whether primary school children's speech processing could be made faster and less effortful via the presentation of visual speech cues (speaker's facial movements), and whether any audio-visual benefit would be modulated by the presence of noise or by characteristics of individual participants. A phoneme monitoring task with concurrent pupillometry was used to measure 7- to 11-year-old children's speech processing speed and effort, with and without visual cues, in both quiet and noise. Results demonstrated that visual cues to speech can facilitate children's speech processing, but that these benefits may also be subject to variability according to children's motivation. Children showed faster processing and reduced effort when visual cues were available, regardless of listening condition. However, examination of individual variability revealed that the reduction in effort was driven by the children who performed better on a measure of phoneme isolation (used to quantify how difficult they found the phoneme monitoring task).